Formation and characterization of polyacrylonitrile (PAN) carbon hollow fiber membranes for gas separation [compact dics] - 207455 Syed Mohd. Saufi Tuan Chik (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Gas)) -Universiti Teknologi Malaysia, 2004